PENDIDIKAN KARAKTER DI TENGAH DERASNYA ARUS MODERNISASI - Cindy Elvira; Elsa; Sovieta Ria (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
This article discusses the challenges and solutions in character education amidst the rapid currents of modernization. Character education is a strategic effort to shape positive attitudes and behaviors in students by instilling essential moral values. However, globalization and technological advancements have shifted local values, resulting in challenges in character development. This study emphasizes the importance of collaboration among schools, parents, and the community in effectively implementing character education. It finds that integrating character values into the curriculum, wisely utilizing technology, and actively involving teachers and families are crucial for creating a generation that is not only intelligent but also possesses strong character.